Tarbiyah Islamiyah dalam Pengembangan Sumber Daya Manusia di Era Gobalisasi - Abd Wahid (Jurnal Ilmiah Islamic Resources, 2022)
The main policy of national development consists of three pillars of education policy, namely: 1) equitable distribution and expansion of access to education, 2) Improving the quality, relevance, and competitiveness of educational outputs; 3) Improving accountability governance and public perception of educational management Social, political, economic, and scientific trends that have emerged in the era of globalization, namely the tendency for economic integration and free trade to emerge, demand management and education services that are global in scope and follow the currents of the times. The complexity of education issues on the one hand and the demand to improve the quality of human resources on the other hand causes the discussion about education to remain interesting and to be reviewed with the hope that this discussion will be able to bring up alternative solutions to develop the quality of human resources through the Tarbiyah Islamiyah route. Tarbiyah Islamiyah offers the concept of a balance between physical and spiritual education, is flexible, and is open to various types of information as long as it is in line with the Qur'an and Sunnah. The findings of this study are expected to contribute to thinking about how to improve the quality of education in Indonesia.